The place of trust in Continuing Professional Learning programmes: supporting authentic reflection in portfolio assessment. Issue 3 (2nd July 2016) - Stocks, Claire; Trevitt, Chris
Abstract: In this paper we consider why academics on Continuing Professional Learning (CPL) programmes often struggle with practice-based learning, and why they can find the reflective portfolio particularly challenging. We first argue that convenors should articulate the differences between 'academic learning' and 'learning in academia' for participants. Furthermore, in an environment where trust has been increasingly replaced by the monitoring of performance, CPL participants can find themselves on unfamiliar learning territory in conditions which are not conducive to risk-taking. We identify how convenors might build the trust required for participants to offer an authentic account of their practice.